GLOBAL CRISIS – AN ECOLONOMIC APPROACH - Constantin Popescu; Alexandru Taşnadi (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2012)
Considering the evolution of life of the whole living, "crisis is a natural manifestation, a form of thesystemic wisdom homeostasis ". Interpreted in terms of Hawa-yen philosophy, life of the "whole living" whichincludes economic and social life as well, crisis stands for excesses and deficits beyond the homeostasis "criticalmass" that disturbs due to the dangers generated by the harmony of integrated integers .As it encompasses both threats and opportunities that encourage creative destruction, crisis heightensawareness of a behavioural change for the sake of a new harmony. The current global crisis, in accordance with theholistic vision, is a systemic crisis a cultural, moral, spiritual and intellectual one that affects negatively all segmentsof life, such the natural, the economic, the social and their interactions, too.As a science of man-made environmental health, ecolonomy interprets the global crisis construed as a deviation ofhuman behaviour and institutional development from the requirements expressed by the harmony of "integratedintegers", the nature of the tunes, coherence and resonance.Deficits of love, authentic knowledge, faith in certainty of hope, wisdom, of education on the meaning oflife and for life, compassion and selflessness, etc, as well as excesses of selfishness, greed, power, domination,poverty, ignorance, waste, freedom without responsibility, etc., engender through their actions human and socialbehaviours which threaten social life and cut through homeostasis.The transformation of the dangers into opportunities- the backward evolution, is a process of whichmetanoia is occurring inside human being where the paradigms find " a nice nest" due to which we come to know,understand, we relate and act.